Filsafat Sains dan Inkuiri Sebagai Pendekatan dalam Membelajarkan Konsep Kekekalan Massa Lavoisier's Law: Philosophy of Science and Inquiry as an Approach to Learning the Concept of Conservation of Mass Lavoisier's Law - Nabuasa, Desi Aryanti; Nahadi, Nahadi; Mellyzar, Mellyzar (Jurnal Filsafat Indonesia, 2024)
The process of learning science is inseparable from the nature of science, which includes knowledge about methods (epistemology), the process of science formation (ontology), and the values  and  beliefs  supporting  the  development of  science  (axiology). This  study  aims  to examine and explain Lavoisier’s law of conservation of mass (Lavoisier Law) through the lenses of epistemology, ontology, and axiology. The research employs a descriptive qualitative method, with document analysis involving the collection, analysis, and interpretation of non-numerical data from various articles published in both national and international journals. The results of this study reveal that the ontological analysis of Lavoisier’s law of conservation of mass can be observed through Lavoisier's experimental facts. The epistemological analysis of Lavoisier’s law explains how Antoine Lavoisier discovered the law and how its validity can be assessed. The axiological analysis of Lavoisier’s law is understood as a study of how the law is applied or utilized and its connection to moral and ethical considerations. The concept of Lavoisier’s law of conservation of mass can be taught using a real-world applications inquiry approach, involving activities such as conducting chemical reaction simulations, product design projects, and real- world case analyses. The real-world applications level can help students improve their skills in data collection and interpretation based on experiments, making predictions, and constructing logical arguments based on scientific evidence, as well as making and justifying decisions based on the obtained evidence